MICROSTRUCTURAL CHANGES DURING OVERTEMPERING OF HIGH-SPEED STEELS - KARAGOZ, S; FISCHMEISTER, HF; ANDREN, HO; CAI, GJ (MINERALS METALS MATERIALS SOC, 1992)
To elucidate the mechanisms determining the creep resistance of high-speed steels during tool service, overtempering at 600-degrees-C has been investigated for two alloys modeling the matrix compositions of AISI M2 and T1. Composition changes and coarsening of the secondary hardening precipitates were studied by transmission electron microscopy and field-ion microscopy with atom probe analysis. Strengthening in the peak-hardened state is due to coherent precipitates of types M2C and MC. During overtempering, M2C coarsens too rapidly to be of importance for the sustained strength of the material. The MC precipitates, on the other hand, are fairly stable. Some coarsening does occur, but the MC population is replenished by a second wave of precipitation which makes use of the roughly 50 pct of carbide-forming elements, carbon, and nitrogen, which remained in solid solution after tempering to the peak-hardened state. This precipitation reaction continues for times of the order of the tool life.
Keywords: ATOM-PROBE; Materials Science